Toys as instructional tools in developing problem-solving skills in children - Clavio, Josefa Carina Veluz (2007)
An exploration on the use of toys as instructional tools in the development of problem-solving skills among preschoolers, this study explained the importance of toys in children's learning environment. The qualitative reseacrh methodology was employed and lessons were developed using Wallace and Maker Problem Solving Wheel. The result of the study showed that among the 24 toys listed, five were the most common and they are the following: puzzles, blocks, simple card and board games, beads and building sets. The success of the study presented opportunities in creating in-service training programs for teachers targeting the use of toys as instructional tool in developing problem solving skills and other thinking skills.